Extrapulmonary Tuberculosis. A Case Report - Maribel Sandrino Sánchez; Mabel Martínez Muñoz; Lázara Basilia Wong Díaz (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2015)
The case of a 49-year-old patient with a 5-month history of general manifestations such as weight loss and weakness, accompanied by enlargement of the lymph nodes in the neck is presented. The physical examination showed an increased volume in the right lateral cervical lymph nodes, forming a mass of approximately two centimeters, without signs of inflammation. Complementary tests revealed several enlarged nodes; the largest was 16 × 14 mm, hypoechoic and behind the right lobe of the thyroid. The node was removed for pathological study, which found a tuberculous lymphadenitis, highly suggestive of tuberculosis (culture positive for mycobacterium tuberculosis on Lowenstein-Jensen medium). Although tuberculosis is now curable, it is not a solved problem. It is important to maintain surveillance and a certain degree of suspicion regarding lung diseases and those affecting other organs.